The growth allometrically Mandalung and histological muscle fiber leg - Sari, Meisji Liana (Indonesian Journal of Animal and Veterinary Sciences, 2003)
This study was conducted to compare the growth alometrically performance especially rate of muscle growth microscopically of Mandalung offspring of Muscovy x Duck (MD) and Duck x Muscovy (DM). Fifty-one Mandalung duck of IE and EI were used. They were fed with 2-type broiler commercial feed, which were starter type (day 1 â week 4) and finisher type (week 4 â week 12). Starter feed contained of 20% protein and 2800 kcal/kg energy while finisher feed contained of 18% protein and 3000 kcal/kg energy. Data on weights of slaughtered body and body parts (head, neck, fore back, rear back, breast, upper leg, lower leg, foot and its membrane) were measured at week 1, 4, 8 and 12. Diameter of muscle fiber was measured at age 8, 10 and 12 weeks, and each slaughter was represented by 1, 2 and 3 ducks. The results showed The growth direction was similar in IE and EI, initiated from head, to the neck, fore back and rear back, and from foot, to the thigh, breast and wings. Diameter of muscle fibers of Mandalung duck offspring of EI were larger (14,49 vs 13,37; 20,02 vs. 15, 24 Î¼m; 23,68 vs. 18, 08 Î¼m) than the IE.Â  Key words: Allometry, histological, muscle fiber